The effect of dadih in BALB/c mice on pro-inflammatory and anti-inflammatory cytokine productions - Ria Kodariah; Hadits Lissentiya Armal; Heri Wibowo; Andi Yasmon (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
The normal microflora formed as commensal bacteria have roles in maintaining homeostasis in the intestine tract. The reduction in the amount and on the diversity of the commensal bacteria lead to gastrointestinal dysbiosis which increase number of pathogens, induce inflammatory and can drive to colorectal cancer. Probiotics can be used to prevent, regulate, and modulate immune response by triggering the development of pathogen-specific memory. Currently, many foreign probiotic products are available in the market that cause the domestic products are less well known. Dadih is an original probiotic’s products originally from West Sumatra, Indonesia. It is made from fermented buffalo milk containing lactic acid bacteria (LAB). The objective of the study was to investigate the effect of dadih pro-inflammatory and anti-inflammatory cytokine production. The study was conducted using male BALB/c mice aged 6-8 weeks with body weight (BW) 20-30 g. Mice were given dadih at doses of 112 mg/20g BW for eight weeks. The results indicated that LAB bacteria in dadih are coccus, Gram-positive bacteria with 3x107 colony-forming units (CFU) and dominated by Lactococcus lactis subsp. lactis. In addition, the increase of both the anti-inflammatory cytokines (IL-10) and pro-inflammatory cytokines (TNF-α and IL-1β) was observed. In conclusion, the dadih can be used to maintain the immune system of mice.